Pregnancy outcomes among Syrian refugee and Jordanian women: a comparative study. (25th May 2017) - Alnuaimi, K.; Kassab, M.; Ali, R.; Mohammad, K.; Shattnawi, K.
Abstract : Aim: To compare pregnancy outcomes of Syrian refugee women and Jordanian women. Background and introduction: In the past few years, thousands of Syrians fled Syria to neighbouring countries such as Jordan as a result of the continuing conflict in their country. Pregnant refugee women are facing many difficulties that increase the prevalence of antenatal complications. However, there is limited awareness of whether Syrian refugee women have different risks of pregnancy outcomes than Jordanian women. Methods: Using a retrospective cohort design, we examined pregnancy outcomes for Syrian refugee ( N  = 616) and Jordanian women ( N  = 644) giving birth at two governmental hospital in northern Jordan, between 1 January 2014 and 31 December 2014. A checklist of 13 variables was utilized. The primary outcome measures were delivery by Caesarean section, maternal complications, low birthweight (<2500 g), APGAR score and preterm delivery (<37 weeks' gestational age). Results: Statistical analysis revealed that refugee mothers had a significant increase in the rate of Caesarean section and higher rate of anaemia, a lower neonates' weight and APGAR scores when compared to their Jordanian counterparts. Discussion: Results were congruent with findings from other studies in the region and worldwide. Conclusion and implications for nursing and health policy: Minimizing inequalities in pregnancy outcomes between Syrian refugees and Jordan women is a healthcare priority. The findings could guide the planning and development of health policies in Jordan that would help to alleviate the situation regarding refugee populations. Action is required by policy makers, specifically targeting public and primary healthcare services, to address the problem of adequately meeting the needs for antenatal care of this vulnerable population.